Messed up on previous question, my apologies...

Use the quadratic formula to solve for x

9x^2-3x-1=0

quadratic formula of ax^2 + bx + c = 0

is x = ( - b +/- √(b^2 - 4ac)) / 2a

9x^2-3x-1 = 0

x = ( - - 3 +/- √(-3^2 - 4*9*-1)) / 2*9

= 3 +/- √(9 + 36 ) / 18

= 3 +/- √(45 ) / 18

= 3 /18 +/- √9*5 / 18

= 1/6 +/- 3 √5 / 18

= 1/6 +/- √5 / 6

= 1/6 + √5 / 6 or 1/6 - √5 / 6 .........................ANSWER

ANSWER IS

x = 1/6 + √5 / 6 or 1/6 - √5 / 6

hope you understood..please message if you have any doubts...thank you

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up